Conservation-Based Management of Children's Character Education on Barrang Lompo Island, Makassar City (Agrikan Jurnal Agribisnis Perikanan, 2022)
Marine pollution is a major threat that can harm human social, economic, and cultural activities. Marine pollution is caused by human activities that do not pay attention to the health of the environment. Marine pollution can be prevented and minimized by employing conservation. The formation of conservation-based children's character is very influential on the sustainability of conservation. Children's character can be formed through education in the family, home, and community environment. The first and foremost environment in forming the foundation of a child's character is the family. Families make a very big contribution to the strength of the foundation of the character of child conservation. Thus, it is necessary to study the management of children's character education in coastal communities that are also direct beneficiaries of marine resources. The purpose of this study is to describe the implementation of conservation-based children's character education management in coastal communities and to find out the effectiveness of conservation-based children's character education in coastal communities. Knowing the management and effectiveness of the management of children's character education in the family environment. This research method uses a quantitative approach with SPSS 25 data analysis. The results obtained from this study are that the character education of children greatly influences the attitude of conservation of children on Barrang Lompo Island. The better the conservation character education management carried out by the family, the stronger the child's conservation attitude will be.
Keywords: Conservation, Children's; Character; Education; Barrang Lompo Island